Fistula Communication by Print and Electronic Media in Bangladesh as facilitated by Bangladesh Health Reporters Forum - Debnath, Sebika; Biswas, Nitta; Huda, Sk Nazmul; Kagoj, Dainik Bhorer (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To describe the role of the Bangladesh Health Reporters Forum in fistula communication through print and electronic media in Bangladesh, to share the lesson learnt. Methods: Sixty reporters and editors from different daily newspapers, satellite TV channels and media institutions were provided a basic workshop on fistula communication by the USAID-supported Fistula Care Plus Project at EngenderHealth Bangladesh from June 2015 to June 2018. They were also supported with information packs including definition, types, diagnosis and referral linkage of fistula by the workshop organizers. Results: Among documented outputs of workshop attendees were 127 documented reports, essays, editorials in the newspapers; eight talk shows in television; and one documentary on fistula. At least 1.2 million people were reached with fistula messages. Conclusions: Media practitioners’ workshops on fistula communication effectively prepared a group of media professionals for contributing in fistula communication. They need information packs help media professionals to develop and publish media products. Technical editorial support is important for upholding the quality of media reports and publications.